Privatized infrastructure the build, operate, transfer approach - Walker, C.; Smith, A. J. (Thomas Telford, 1995)
The worldwide championing of the privatisation concept has led many governments to look for new ways of identifying and funding their infrastructure needs. 'The Build Operate/Own Transfer' arrangement for infrastructure procurement has subsequently evolved,.